TINJAUAN TEORITIS: PERAN REKSA DANA SYARIAH DALAM MENINGKATKAN INKLUSI KEUANGAN DI INDONESIA - Siti Chairinnisa Hardi; Syafitri Ronauli Daulay; Muhammad Ziqhri Anhar Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Islamic mutual funds are investment instruments that have been growing rapidly and are considered to play an important role in promoting financial inclusion in Indonesia. This study aims to examine the contribution of Islamic mutual funds in expanding access to formal financial services and to identify the challenges faced in their development. The method employed is a literature review by analizing various studies, reports, and empirical data related to the growth of the Islamic mutual fund industry. The findings indicate that Islamic mutual funds can broaden public participation in investment through low entry capital requirements, compliance with sharia principles that enhance trust, and performance that remains competitive compared to conventional instruments. Digitalization further strengthens the distribution and accessibility of these products, particularly among younger generations. However, challenges such as low financial literacy, uneven product distribution, and limited innovation remain as barriers. Overall, Islamic mutual funds have the potential to serve as strategic instruments in realizing an inclusive and sustainable financial system in Indonesia. These findings imply the need for synergy among regulators, industry players, and educational institutions to strengthen financial literacy, expand distribution channels, and enhance innovation in the development of Islamic mutual funds.